2010
DOI: 10.1073/pnas.0911561107
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for initiator-tRNA in pre-mRNA splicing regulation

Abstract: The translation initiator-tRNA plays a crucial role in the initiation of protein synthesis in both prokaryotic and eukaryotic cells, by employing specific base pairing between its anticodon triplet CAU and the general initiation codon AUG in the mRNA. Here we show that the initiator-tRNA may also act, in a manner that is independent of its role in protein translation, as a pre-mRNA splicing regulator. Specifically, we show that alternative splicing events that are induced by mutations in the translation initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 32 publications
0
59
0
Order By: Relevance
“…In previous studies, we have shown that the apparent lack of expression of latent mRNAs under normal growth conditions could not be attributed to degradation by NMD or any other NMD-like RNA surveillance mechanism [(5) and summarized in Supplementary Table S1 of (34)]. Our data have suggested an alternative model, whereby splicing involving latent sites is suppressed such that the generation of PTC-bearing mRNAs is avoided (3,18,31,34).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In previous studies, we have shown that the apparent lack of expression of latent mRNAs under normal growth conditions could not be attributed to degradation by NMD or any other NMD-like RNA surveillance mechanism [(5) and summarized in Supplementary Table S1 of (34)]. Our data have suggested an alternative model, whereby splicing involving latent sites is suppressed such that the generation of PTC-bearing mRNAs is avoided (3,18,31,34).…”
Section: Resultsmentioning
confidence: 71%
“…Our data have suggested an alternative model, whereby splicing involving latent sites is suppressed such that the generation of PTC-bearing mRNAs is avoided (3,18,31,34). However, we see here that subjecting cells to stresses appeared to have abrogated this suppression, leading to the generation of latent mRNAs.…”
Section: Resultsmentioning
confidence: 88%
“…A new cloning method provided evidence for widespread expression of dsRNAs in mouse brain, suggesting that pre-mRNA regulation by antisense RNAs is much more common than previously anticipated (Shen et al, 2011). tRNAs are another emerging regulation by RNA where the initiator tRNA, devoid of a loaded methionine, can regulate alternative splicing events that depend on the AUG start codon for their usage (Kamhi et al, 2010). …”
Section: 0 Mechanism Of Alternative Splicingmentioning
confidence: 99%
“…Second, while the translation initiator tRNA i Met plays a crucial role in the initiation of protein synthesis, it also has the ability to act as a pre-mRNA splicing regulator in a manner independent of its role in protein synthesis. Specifically, alternative splicing events resulting from AUG codon mutations are suppressible by initiator tRNA i Met variants harboring anticodon mutations that match the AUG mutations (Kamhi et al, 2010). This mechanism of regulation of splicing appears to play a role in quality control of splicing in the cell nucleus, preventing the generation of premature termination codons.…”
Section: Non-canonical Functions Of Trnamentioning
confidence: 99%